2004
DOI: 10.1182/blood-2003-11-3909
|View full text |Cite
|
Sign up to set email alerts
|

Human bone marrow stromal cells inhibit allogeneic T-cell responses by indoleamine 2,3-dioxygenase–mediated tryptophan degradation

Abstract: IntroductionHuman bone marrow stromal cells (MSCs), more recently referred to as mesenchymal stem cells, are capable of differentiating along multiple mesenchymal lineages in addition to supporting hematopoiesis. 1,2 Due to their potential for differentiation into osteocytes, chondrocytes, myocytes, and adipocytes, MSCs have emerged as a promising tool for clinical applications such as tissue engineering and cell and gene therapy. 3,4 MSCs are of inherently low immunogenicity and, more importantly, are capable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

42
1,228
5
28

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,528 publications
(1,329 citation statements)
references
References 22 publications
42
1,228
5
28
Order By: Relevance
“…MSCs express indoleamine 2,3-dioxygenase (IDO)-an immune regulatory enzyme that catalyses the degradation of tryptophan via the kynurenine pathway-and exhibit functional IDO activity and IDO-dependent apoptotic effects on allogeneic human T cells upon stimulation with IFN-γ (Meisel et al, 2004;Plumas et al, 2005). In vivo in mice with EAE, transplanted syngeneic MSCs prevent relapses and promote myelin repair via an IFN-γ-dependent mechanism that induces IDO in CD11c + DCs and leads to the inhibition of antigen reactivity and disease spread (Matysiak et al, 2008(Matysiak et al, , 2011.…”
Section: Paracrine Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…MSCs express indoleamine 2,3-dioxygenase (IDO)-an immune regulatory enzyme that catalyses the degradation of tryptophan via the kynurenine pathway-and exhibit functional IDO activity and IDO-dependent apoptotic effects on allogeneic human T cells upon stimulation with IFN-γ (Meisel et al, 2004;Plumas et al, 2005). In vivo in mice with EAE, transplanted syngeneic MSCs prevent relapses and promote myelin repair via an IFN-γ-dependent mechanism that induces IDO in CD11c + DCs and leads to the inhibition of antigen reactivity and disease spread (Matysiak et al, 2008(Matysiak et al, , 2011.…”
Section: Paracrine Signalingmentioning
confidence: 99%
“…Data in Table 1 are in part summarized in (Chamberlain et al, 2008;Hall et al, 2006;Martino and Pluchino 2006;Pluchino et al, 2009b;Rojewski et al, 2008;Uccelli et al, 2008;Yuan et al, 2011). (Cusimano et al, 2012;Jaderstad et al, 2010) aracrine IDO-kynurenine MSCs (h) T cells, DCs T cell apoptosis, inhibition of antigen presentation (Lanz et al, 2010;Matysiak et al, 2008Matysiak et al, , 2011Meisel et al, 2004;Plumas et al, 2005 Bonnamain et al, 2012;Chabannes et al, 2007;Moll et al, 2011) Paracrine VEGF NPCs Microglia/macrophages Inhibition of microglial activation, proliferation and phagocytosis (Horie et al, 2011;Kim et al, 2009a;Mosher et al, 2012) Paracrine LIF NPCs Th17 cells Inhibition of Th17 cell differentiation (Cao et al, 2011;Horie et al, 2011;Kim et al, 2009a;Mosher et al, 2012) Paracrine Galectins MSCs/NPCs T cells Inhibition of T cell proliferation (Gieseke et al, 2010;Sioud 2011;Yamane et al, 2010Yamane et al, , 2011 Endocrine/Paracrine TSG-6 MSCs Macrophages Inhibition of macrophage activation, proliferation and phagocytosis (Fisher-Shoval et al, 2012;Lee et al, 2009;Roddy et al, 2011) EVs miR transfer MSCs/NPCs Multiple Post-transcriptional regulation (Bruno et al, 2009;Chen et al, 2010;…”
mentioning
confidence: 99%
“…Inhibition of T cell proliferation by MSC appears to be subsequent both to cell-to-cell interaction and to the release of soluble factors, and it is conceivable that discrepant findings reported in the literature reflect differences in the experimental conditions used [13,14,16,48,49]. TGF-b1 and HGF [13], indoleamine 2,3-dioxygenase (IDO) [50] and prostaglandin E2 (PGE-2) [46] represent MSC-derived molecules that have been proposed to exert immunomodulatory activity on T cell responses. However, most of these results need to be confirmed, and it is likely that key molecules will be identified through functional molecular profiling of the MSC transcriptome.…”
Section: Msc and T Lymphocytesmentioning
confidence: 99%
“…Local decrease of tryptophan and an increase of kynurenine are associated with immunosuppression and a shift from a Th1 to a Th2 response [14]. Expression of IDO in MSCs is induced by interferon-g (IFN-g) [12].We have already demonstrated that eosinophilic granulocytes (Eos) are attracted by necrotic material and respond to DAMPs by releasing reactive oxygen species, which are capable of oxidizing native/active DAMPs [3], including HMGB1 [3]. Oxidized DAMPs lose their capacity to further attract and activate Eos [3].…”
mentioning
confidence: 99%